Generation of intra- and interspecific Saccharomyces hybrids with improved oenological and aromatic properties - Perez, Maria Dolores; Denat, Marie; Pérez-Través, Laura; Heras, José María; Guillamón, José Manuel; Ferreira, Vicente; Querol, Amparo (Wiley, 2022)
Non-wine yeasts could enhance the aroma and organoleptic profile of wines. However, compared to wine strains, they have specific intolerances to winemaking conditions. To solve this problem, we generated intra- and interspecific hybrids using a non-GMO technique (rare-mating) in which non-wine strains of S. uvarum, S. kudriavzevii and S. cerevisiae species were crossed with a wine S. cerevisiae yeast. The hybrid that inherited the wine yeast mitochondrial showed better fermentation capacities, whereas hybrids carrying the non-wine strain mitotype reduced ethanol levels and increased glycerol, 2,3-butanediol and organic acid production. Moreover, all the hybrids produced several fruity and floral aromas compared to the wine yeast: β-phenylethyl acetate, isobutyl acetate, γ-octalactone, ethyl cinnamate in both varietal wines. Sc × Sk crosses produced three- to sixfold higher polyfunctional mercaptans, 4-mercapto-4-methylpentan-2-one (4MMP) and 3-mercaptohexanol (3MH). We proposed that the exceptional 3MH release observed in an S. cerevisiae × S. kudriavzevii hybrid was due to the cleavage of the non-volatile glutathione precursor (Glt-3MH) to detoxify the cell from the presence of methylglyoxal, a compound related to the high glycerol yield reached by this hybrid. In conclusion, hybrid generation allows us to obtain aromatically improved yeasts concerning their wine parent. In addition, they reduced ethanol and increased organic acids yields, which counteracts climate change effect on grapes.